Aritmia - Rahmad Syukran; Emelda Emelda (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2026)
Arrhythmia is a disorder related to the rate or rhythm of the heartbeat. Arrhythmias can be categorized into two types based on heart rate: tachyarrhythmias and bradyarrhythmias. The most commonly encountered arrhythmia is atrial fibrillation, with an estimated 46.3 million cases worldwide. It is projected that by 2050, the prevalence of atrial fibrillation will continue to increase, reaching 6–16 million cases in the United States, 14 million cases in Europe, and 72 million cases in Asia. In Indonesia, arrhythmias are often not diagnosed early because the initial symptoms are frequently mild, asymptomatic, or unrecognized by patients. Early detection of arrhythmias in Indonesia is also limited to certain healthcare facilities that have access to cardiac diagnostic technologies such as electrocardiography (ECG) and Holter monitoring. Public awareness and understanding of arrhythmias and their potential dangers remain low, resulting in many patients becoming aware of their condition only after experiencing serious complications. Possible complications arising from cardiac rhythm disturbances include syncope, hypo- or hypertension, dyspnea, and others. However, the most severe complications are sudden cardiac death and thromboembolism, which can lead to stroke and other vascular disorders.